A novel flow cytometry panel to identify prognostic markers for steroid-sensitive forms of idiopathic nephrotic syndrome in childhood - Riganati, Martina; Zotta, Federica; Candino, Annalisa; Conversano, Ester; Gargiulo, Antonio; Scarsella, Marco; Lo Russo, Anna; Bettini, Chiara; Emma, Francesco; Vivarelli, Marina; Colucci, Manuela (Frontiers in Immunology, 2024)
Introduction The clinical evolution of steroid-sensitive forms of pediatric idiopathic nephrotic syndrome (INS) is highly heterogeneous following the standard treatment with prednisone. To date, no prognostic marker has been identified to predict the severity of the disease course starting from the first episode. Methods In this monocentric prospective cohort study we set up a reproducible and standardized flow cytometry panel using two sample tubes (one for B-cell and one for T-cell subsets) to extensively characterized the lymphocyte repertoire of INS pediatric patients. A total of 44 children with INS at disease onset were enrolled, sampled before and 3 months after standard induction therapy with prednisone and followed for 12 months to correctly classify their disease based on relapses. Age-matched controls with non immune-mediated renal diseases or with urological disorders were also enrolled. Demographical, clinical, laboratory and immunosuppressive treatment data were registered. Results We found that children with INS at disease onset had significantly higher circulating levels of total CD19+ and specific B-cell subsets (transitional, mature-naïve, plasmablasts/plasmacells, CD19+CD27+, unswitched, switched and atypical memory B cells) and reduced circulating levels of Tregs, when compared to age-matched controls. Prednisone therapy restored most B- and T-cell alterations. When patients were subdivided based on disease relapse, relapsing patients had significantly more transitional, CD19+CD27+ memory and in particular unswitched memory B cells at disease onset, which were predictive of a higher risk of relapse in steroid-sensitive patients by logistic regression analysis, irrespective of age. In accordance, B-cell dysregulations resulted mainly associated with steroid-dependence when patients were stratified in different disease severity forms. Of note, Treg levels were reduced independently from the disease subgroup and were not completely normalized by prednisone treatment. Conclusion We have set up a novel, reproducible, disease-specific flow cytometry panel that allows a comprehensive characterization of circulating lymphocytes. We found that, at disease onset, relapsing patients had significantly more transitional, CD19+CD27+ memory and unswitched memory B cells and those who are at higher risk of relapse had increased circulating levels of unswitched memory B cells, independently of age. This approach can allow prediction of clinical evolution, monitoring of immunosuppression and tailored treatment in different forms of INS.